Education for extinction American Indians and the boarding school experience, 1875 - 1928 - Adams, David W. (Univ. Press of Kansas, 1995)
Education for Extinction offers the first comprehensive account of this dispiriting effort. Much more than a study of federal Indian policy, this book vividly details the day-to-day experiences of Indian youths living in a "total institution" designed to reconstruct them both psychologically and culturally. Based upon extensive use of government archives, Indian and teacher autobiographies, and school newspapers, it is essential reading for anyone interested in Western history, Native American studies, American race relations, educational history, or multi-culturalism